Phylloplane mycoflora of Gerbera spp. and their Pathogenic potentiality (Journal of Bangladesh Academy of Sciences, 2014)
Two types of symptoms, blight and anthracnose, were recorded on two species of Gerbera viz. Gerbera aurantiaca L. and Gerbera viridifolia L. The most common fungal species isolated from Gerbera spp. were Alternaria citrii, A. tennuisssima, Aspergillus flavus, A. fumigatus, A. niger, A. terreus, Bipolaris hawaiiensis, Chaetomella raphigera, Cladosporium cladosporoides, Colletotrichum capsici, C. coffeanum, C. dematium, C. gleosporioides, C. lindemuthianum, C. musae, C. orbiculare, Colletorichum sp.1, Colletotrichum sp.2, Colletotrichum sp.3, Colletotrichum sp.4, Curvularia clavata, C. lunata, Fusarium nivale, F. semitectum, Phomopsis sp., Penicillium sp., Pestalotia sp., Rhizopus stolonifer, Trichoderma viride, one cleistothecial ascomycetes and one sterile fungus. The frequency percentage of association of Colletotrichum spp. with Gerbera spp. was higher than any other fungi. Bipolaris hawaiiensis is a new record for Bangladesh. Among the isolated fungi Alternaria citrii, A. tennuissima, Colletotrichum capcisi, C. dematium, C. coffeanum and Curvularia clavata were found to be pathogenic to Gerbera plant. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17562 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 211-217, 2013